Analytic Philosophy of Religion - Harris, James Franklin. author. aut Link
VIII, 433 p.
Keywords: When Gene Long, editor of Kluwer's Handbook of Contemporary Philosophy of Religion Series, first invited me to write the volume on Analytic Philosophy of Religion, I accepted with great enthusiasm. My only explanation for that enthusiasm now is that I was younger and more naive at the time. Soon after starting work on the volume, my enthusiasm was dampened by the daunting magnitude of the task. I began as a sprinter and quickly settled into the pace of a long-distance runner. Although I considered myself well read in the subject, I soon discovered that I had a great deal of research to do to be confident that I had considered all of the major contributions to the various discussions, issues, and of religion. As I read more and more problems found within analytic philosophy books and articles, I realized that I had rushed into a territory already well trodden by the angels. I am greatly impressed by the sophistication and subtlety of philosophical argument that characterize the different debates in contemporary analytic philosophy of religion. This volume covers a vast amount of material. I have endeavored to provide the fairest possible reading of different authors, and, in cases where I include my own critical evaluations and develop my own positions, I have endeavored to provide the strongest possible interpretations of the positions I criticize.